2011
DOI: 10.1111/j.1440-1746.2010.06429.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus genotype B results in better immediate, late and sustained responses to peginterferon‐alfa in hepatitis‐B‐e‐antigen‐positive patients

Abstract: Pretreatment HBeAg S/Co ratio ≤ 200 and HBV genotype B were major determinants for treatment response to peginterferon. Genotype-B-infected patients had higher probability of delayed HBeAg clearance and sustained response. Rapid decrease of HBeAg titer was useful on treatment predictor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…HBV genotypes have been associated with variable clinical outcomes and different responses to IFNα and NRTI treatments that are discussed below (Chien et al, 2003, Hsieh et al, 2009, Chen et al, 2011, Lin and Kao, 2011). Since the S and P gene sequences partially overlap with each other but are translated in different reading frames, single nucleotide changes among different HBV genotypes may or may not affect the amino acid composition of both gene products (Figure 2) (Mizokami et al, 1997).…”
Section: Hbv Serotypes and Genotypesmentioning
confidence: 99%
“…HBV genotypes have been associated with variable clinical outcomes and different responses to IFNα and NRTI treatments that are discussed below (Chien et al, 2003, Hsieh et al, 2009, Chen et al, 2011, Lin and Kao, 2011). Since the S and P gene sequences partially overlap with each other but are translated in different reading frames, single nucleotide changes among different HBV genotypes may or may not affect the amino acid composition of both gene products (Figure 2) (Mizokami et al, 1997).…”
Section: Hbv Serotypes and Genotypesmentioning
confidence: 99%
“…Perinatal transmission of HBV is strongly associated with HBeAg positivity in the mother (11) and HBeAg seroconversion is considered as a marker for a sustained therapeutic response (12). Quantitative assays for HBeAg are not routinely available, and HBeAg levels are expressed as serial dilutions of a reference sample from the Paul Ehrlich Institute (Langen, Germany) (13).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative assays for HBeAg are not routinely available, and HBeAg levels are expressed as serial dilutions of a reference sample from the Paul Ehrlich Institute (Langen, Germany) (13). It has been suggested that the evaluation of the HBeAg sample to cut-off ratio (S/co ratio) could be useful for HBV diagnosis and treatment (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…Nine studies involving 1855 participants (genotype B group = 802, genotype C group = 1053) reported the rate of sustained ALT normalization. Luo et al .…”
Section: Resultsmentioning
confidence: 99%
“…One review, which evaluated the influence of HBV genotype on the outcome of IFN therapy, has been published before . The review did not include the recent nine studies . An update of the meta‐analysis is needed to provide stronger and more general support the relationship between HBV genotype B and C and response to IFN therapy in HBeAg‐positive CHB patients.…”
Section: Introductionmentioning
confidence: 99%